Traumas bucomaxilofaciais decorrentes dos acidentes automobilísticos entre os anos de 2002 a 2011 - Silva, Thiago Vinicius Orbato [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Traumas have great importance in contemporary society. According to the World Health Organization, trauma are among the leading causes of death and morbidity in the world and are of great importance as it provides emotional, functional and possibility of permanent deformities repercussions. The large amount of lesions on the face due to the huge exposure and little protection in this region, which often causes serious injury. The injuries of the head and face may represent 50% of all traumatic deaths. Maxillofacial trauma resulting from traffic accidents have been identified as one of the etiological factors that predispose the occurrence of various types of physical trauma, being the principal cause of death in the age range from five to forty years of age worldwide. With urbanization and technological development of automobiles, associated with poor income distribution, negligence, imprudence and incompetence became alarming increase in traffic accidents. Because of maxillofacial injuries are caused by the vast majority of traffic accidents thus, this paper aimed to investigate and study the prevalence of facial fractures and associated factors in patients who have suffered car accidents prioritizing epidemiological data (age, gender, occupation, place of origin), etiologies of fractures, place (jaw, zygomatic, maxillary, frontal and nasal bones), and treatment (invasive and noninvasive) whose patients were seen by the extension project entitled Surgical-Dental Care for patients with trauma Maxillofacial in outpatient level and Hospital between the years 2002 and 2011.. After a series of 237 patients with a history of trauma by car accident, it was found that: a) 71.7% were male while 28.3% were female; b) the age of highest incidence was 21 to 30 years, with 24.5%. Among the days of the week, traffic accidents occurred in greater numbers...

Os traumas apresentam grande importância na sociedade contemporânea. Segundo dados da Organização Mundial de Saúde, os traumas estão entre as principais causas de morte e morbidade no mundo e possuem grande importância uma vez que apresenta repercussões emocionais, funcionais e possibilidade de deformidades permanentes. A grande quantidade de lesões na face deve-se à enorme exposição e a pouca proteção desta região, o que acarreta frequentemente lesões graves. As lesões da cabeça e da face podem representar 50% de todas as mortes traumáticas. Traumas bucomaxilofaciais decorrentes dos acidentes automobilísticos têm sido apontados como um dos fatores etiológicos que predispõem a ocorrência dos diversos tipos de traumas corporais, sendo o principal responsável de causa de morte na faixa etária dos cinco aos quarenta anos de idade em todo o mundo. Com a urbanização e o desenvolvimento tecnológico dos automóveis, associados com a má distribuição de renda, negligências, imprudências e imperícias tornou alarmante o aumento dos acidentes automobilísticos. Pelo fato dos traumatismos bucomaxilofaciais serem desencadeados pela grande maioria dos acidentes de trânsito, desta forma o presente trabalho teve o objetivo de investigar e estudar a prevalência de fraturas faciais e fatores associados em pacientes que sofreram acidentes automobilísticos priorizando os dados epidemiológicos (idade, sexo, profissão, procedência), etiologias das fraturas, local (mandíbula, zigomático, maxila, frontal e ossos nasais), e seu tratamento (invasivo e não-invasivo) cujos pacientes foram atendidos pelo projeto de extensão intitulado Atendimento Cirúrgico-Odontológico para pacientes com traumatismo bucomaxilofacial em Nível Ambulatorial e Hospitalar entre os anos de 2002 e 2011. Após uma casuística de 237 pacientes...
Keywords: Traumatismos maxilofaciais; Acidentes de trânsito; Fraturas mandibulares; Traumatismos faciais; Maxillofacial Injuries